Juridical Review of Copyright Protection of Cinematographic Works (Film) in Illegal Dissemination of Film on Social Media: Analysis based on Law Number 28 of 2014 Concerning Copyright - Ajeng Rizky Andria Ramadhani; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
With the passage of time, the internet and social media have become a necessity and are very easy to use by the public. However, with the ease of use of the internet, some people who want to watch movies but don't want to watch in the places provided have been abused, which ends up using social media TikTok as a platform for streaming movies. This can lead to copyright issues which are regulated in Law Number 28 of 2014. The distribution of the film is considered illegal and can damage the economic rights and moral rights of creators of copyrighted works and there are sanctions for those who violate them. The purpose of this study was to find out the provisions on copyright and legal responsibility for perpetrators who violate Law Number 28 of 2014. This study used normative research methods and the data used used secondary data and then analyzed using deductive thinking methods. The results of this research originate from Law Number 28 of 2014 which regulates Copyright. Then it is used as a data source to analyze the sanctions given to persons who violate copyright on social media.